The Relationship Between The Accuracy of Triage Assessment And The Success Rate Management of Head Injury Patients (Literature Review) - Rumtutuly, Hardy Oktavianus Meil; Laoh, Joice M.; Tuegeh, Johana (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
Background: North Sulawesi has the third highest head injury rate. Head injuries in North Sulawesi are mostly experienced in road accidents. Handling in the triage room determines the success of handling head injury patients. Where the role of nurses in sorting patients based on the severity of injury determines the appropriate action. Purpose: The purpose of this study is to review one article and another about the relationship between the accuracy of triage assessment and the success rate of handling head injury patients based on literature review. Methods: this uses Literature Review research, articles are collected from search results on two databases such as sciencedirect and Google Scholar. With the criteria for articles published in 2015-2020, researchers obtained 20 articles and then made a selection using the year limit, according to the exclusion criteria and according to the inclusion criteria. And only 5 articles were used that fit the research topic. Results: research from the five articles showed a relationship between triage assessment and the success rate of handling head injury patients despite different research methods. Conclusion: based on the results of research and discussion, it can be concluded that the accuracy of triage assessment can determine the success of handling head injury patients. Keywords: Triage assessment, head injury patient management